Desigualdade social e informática educativa, desafios e oportunidades no contexto do município de Santarém - PA. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Or present work visa to start a discussion about what poverty is, social inequality and education, with no base for the last year, no public system of ensino, milhões of some impoverished, beneficiaries of the Bolsa Família Program. Analyzing maneira as these students are only received and treated not school environment, the challenges faced by them, but also by their teachers, especially not that tange a formation of new curricula capable of assisting na formação dessas crianças and adolescents, not a sc ope of uma appropriação cidadã das TICs na educação, as a way of instrumentalizing these expropriated coletives not a sense of time and voice in a public sphere increasingly interconnected.
Keywords: Desigualdade social; Pobreza; Currículo; Informática Educativa; Cultura Digital; CNPQ:: CIÊNCIAS EXATAS E DA TERRA